THE ANALYSIS OF STUDENTS’ TEAM ACHIEVEMENT DIVISIONS (STAD) USED IN LEARNING PRACTICE OF TRANSLATING AND INTERPRETING - Anita Rakhman; Isry Laela Syatroh (Eltin Journal : Journal of English Language Teaching in Indonesia, 2015)
This research deals with The Analysis of Student Teams Achievement Division (STAD) used in Learning Practice of Translating and Interpreting. This research explores the implementation of STAD and find out the advantages and disadvantages of STAD used in learning Practice of Translating and Interpreting. The objective of the research was to motivate students and encourage them to be active in learning, to accelerate student achievement, to improve behavior in learning, and to find out the students’ ability with STAD method. Data collection technique focused on participant observation, interviews, and documentation. STAD is one type of cooperative learning model using small groups with a number of members of each group of 4-5 students in heterogenic way. It begins by delivering the objectives of learning, delivering of material, group activities, quizzes and group rewards. STAD method also is an effective method of cooperative learning. As with other learning methods, STAD method also has advantages and disadvantages. In the learning process there are good interactions among students, good attitude, increased interpersonal skills. It’s effective in increasing student participation and can train students to be more focus, more concentrate in answering questions from the teacher. It can make students eager to learn. But if the chief of the group can not resolve conflicts that arise constructively, it will be less effective in a group work. And if the number of groups is not considered, that is less than four, it would tend to withdraw and less active during the discussion. And if the number of groups of more than five, then chances for them to be passive in task completion Keywords: Student Team Achievement Division (STAD), Cooperative Learning.